2019
DOI: 10.1021/acsami.9b12370
|View full text |Cite
|
Sign up to set email alerts
|

Low-Temperature Preparation of Mechanically Robust and Contamination-Resistant Antireflective Coatings for Flexible Polymeric Glasses via Embedding of Silica Nanoparticles and HMDS Modification

Abstract: Mechanical and contamination-resistant properties are the most crucial and challenging issues that impede the practical applications of sol–gel antireflective (AR) coating. In this paper, we report a low-temperature vapor surface treatment strategy for the partial embedding and surface functionalization of silica nanoparticles (SNPs) on flexible polymeric glass substrates. SNPs, which were synthesized via the Stöber method, were partially embedded into the polymeric glass substrates by vapor-phase surface tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(3 citation statements)
references
References 54 publications
(68 reference statements)
0
3
0
Order By: Relevance
“…The results indicated that the nanocomposite coating showed a reduction in the reflectance (6.29%). Wang et al [33] reported the surface functionalization of silica nanoparticles on polycarbonate (PC) and polymethylmethacrylate (PMMA) glass substrates. The obtained results showed that the coated PC/PMMA substrates exhibit high optical transmission (98%), superior abrasion resistance after 100 cycles and contamination resistance performed at room temperature.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
“…The results indicated that the nanocomposite coating showed a reduction in the reflectance (6.29%). Wang et al [33] reported the surface functionalization of silica nanoparticles on polycarbonate (PC) and polymethylmethacrylate (PMMA) glass substrates. The obtained results showed that the coated PC/PMMA substrates exhibit high optical transmission (98%), superior abrasion resistance after 100 cycles and contamination resistance performed at room temperature.…”
Section: Uv-vis Spectroscopymentioning
confidence: 99%
“…A hydrophobic AR film on polymer substrates is obtained by the sol–gel method with an ammonia vapor treatment, and it shows the mechanism of Ostwald-ripening-type structural modification under vapor treatment [ 12 ]. Then, ammonia is used with organic silane to modify film in the later study, an AR coating with good stability in different environment is obtained by the combined vapor phase surface treatment [ 13 , 14 ]. The vapor treatment process is simple to implement and can be carried out at room temperature and atmospheric pressure with minimal equipment requirements and minimal substrate handling [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…The multiple hydrophobic functionalized SiO 2 NPs have been prepared through the efficient reaction between the amino group containing SiO 2 NPs and the isocyanate containing hydrophobic surface modifiers synthesized by normal alcohols. The moisture-proof property of this coating depends on hydrophobic groups exposed on the coating surface, and the antireflective property of the coating relies on their porous structure formed by random or ordered stacking of hydrophobic nanoparticles. However, hydrophobic modifying of nanoparticles or coatings has an adverse influence on the adhesive force between coatings and the substrates, which results in the coating with poor mechanical properties .…”
Section: Introductionmentioning
confidence: 99%